A practice research study concerning homeless service user involvement with a programme of social support work delivered in a specialized psychological trauma service - Archard, P.J.; Murphy, David (Wiley, 2015)
Homeless people are a population known to be highly vulnerable to trauma, in triggering events to becoming homeless and the considerable social isolation, discrimination, and adversity suffered when homeless. Currently, there is a paucity of research into mental health service delivery to homeless persons and the influence it imparts in individual lives. This article presents a qualitative ‘practice research’ study into a pilot programme of social support work delivered in a specialized psychological trauma service to homeless service users. The programme was grounded in a non-directive, person-centred approach and staffed by student social workers. The study aim was to explore the support work programme as it was received by service users domiciled in supported housing for homeless persons, encompassing experiencing the programme, worker-service user engagement and contextual influences bearing upon positive outcomes. Narrative interviews gathered the impressions of service users and support workers and the data arising from these interviews was analysed thematically. Service user participants valued support work that combined practical and relational elements, but would have preferred a longer-term involvement. They also spoke of feelings of disconnection and estrangement from their peers in the supported accommodation and their families. The worker participants valued the flexibility of person-centred work tailored to service users' individual needs and echoed service user concerns around the short-term nature of their involvement. Psychiatric nurses carrying out, or supervising, mental health support work with homeless service users should be mindful of the potential impact of temporary staffing arrangements on continuity of care. They should also consider how working from a person-centred perspective and addressing client's practical needs may aid in developing rapport and trust with homeless service users.